ANALYSIS OF STUDENTS' ABILITY TO CONSTRUCT ARABIC SENTENCES THROUGH THE COMPLETE SENTENCE METHOD IN GRADE X AT MAS AL-WASHLIYAH 12 PERBAUNGAN - Saidah, Siti; Taufiq, Muhammad (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze students' ability to construct Arabic sentences through the application of the Complete Sentence method among tenth grade students of MAS Al-Washliyah 12 Perbaungan. The research was motivated by the low proficiency of students in combining vocabulary into grammatically correct sentences based on the rules of nahwu and sharaf. Many students faced difficulties due to their limited mastery of mufradat (vocabulary), lack of understanding of sentence structures, and low self-confidence in sentence construction.This study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the Complete Sentence method helps students understand sentence structure contextually, enhances participation, and improves their skills in composing complete sentences by engaging in activities that require them to complete unfinished sentences. Although challenges remain such as varying levels of students' basic abilities and limited class time gradual guidance and repeated practice were found to significantly improve students' oral and written performance. Therefore, the Complete Sentence method proved effective in enhancing students' ability to construct Arabic sentences at MAS Al-Washliyah 12 Perbaungan